Multimedia Drill And Practice Belajar Kosa Kata Bahasa Jepang Untuk Siswa Lintas Minat - Kartika Suci Lestari; Yerry Soepriyanto; Arafah Husna (Universitas Negeri Malang, 2020)
Abstract: The cross-interest program is a new program and policy by government in the curriculum 2013. The program aims to give students the opportunity to learn science outside the specialization program. However, there have obstacles to implementation it, as happened in the learning process of SMA Muhammadiyah 2 Genteng in class X of across Japanese interests. Students want teachers to use a variety of instructional media to improve their mastery of vocabulary that they feel difficult to learnt. So, in this research and development aims to produce multimedia learning products to facilitate and motivate students to always learning. This multimedia drill and practice designed to according what students need to improve their mastery of more new vocabulary in Japanese. In this research and development using the Lee & Owens method. Obtained data results from media experts namely 98.3% and 91.8% material experts. From these data shows that multimedia learning in the criteria (76% -100%) valid and feasible based on the percentage table of eligibility. Then the multimedia drill and practice is ready to use in the learning process.Abstrak: Program lintas minat merupakan program dan kebijakan baru pemerintah pada kurikulum 2013. Program tersebut bertujuan untuk memberi kesempatan siswa untuk mempelajari suatu keilmuan di luar program peminatan. Namun, terdapat hambatan dalam pelaksanaanya seperti yang terjadi pada proses pembelajaran SMA Muhammadiyah 2 Genteng di kelas X lintas minat bahasa Jepang. Siswa menginginkan agar guru menggunakan variasi multimedia pembelajaran untuk meningkatkan penguasaan kosa kata yang mereka anggap sulit. Maka pada penelitian dan pengembangan ini bertujuan menghasilkan produk multimedia pembelajaran untuk mempermudah belajar agar siswa semangat belajar. Multimedia drill and practice ini dirancang sesuai kebutuhan siswa yakni untuk meningkatkan penguasaan kosa kata baru dalam bahasa jepang. Pada penelitian dan pengembangan ini menggunakan metode Lee & Owens. Didapatkannya data hasil dari ahli media yaitu 98,3% dan ahli materi 91,8%. Dari data tersebut menunjukkan multimedia pembelajaran dalam kriteria (76%-100%) valid dan layak berdasarkan presentase tabel kelayakan. Maka multimedia drill and practice tersebut siap digunakan dalam proses pembelajaran.